ANALISIS KOMPREHENSIF TERHADAP PENGARUH IMPLEMENTASI GOOD CORPORATE GOVERNANCE DAN KEPATUHAN SYARIAH TERHADAP STABILITAS SERTA KINERJA KEUANGAN LEMBAGA KEUANGAN ISLAM DI INDONESIA - Rendi Pohan; Sultan Arrumi Yahya; Bagus Yudistira; Muhammad Arfan Harahap (CV. Barokah Publsiher, 2025)
This study aims to comprehensively analyze the influence of Good Corporate Governance (GCG) implementation and Sharia compliance on the stability and financial performance of Islamic financial institutions in Indonesia. The application of sound governance and adherence to Sharia principles are fundamental in maintaining public trust, enhancing operational efficiency, and ensuring the sustainability of Islamic financial institutions amid the dynamic modern financial system. This research employs a quantitative approach using secondary data obtained from annual financial reports and corporate governance disclosures of Islamic financial institutions during the observation period. Financial performance and stability are measured through profitability ratios and financial stability indicators, while GCG and Sharia compliance are assessed based on regulatory guidelines and established Sharia standards. The results indicate that the implementation of Good Corporate Governance and Sharia compliance has a positive and significant effect on both financial stability and performance of Islamic financial institutions. These findings suggest that strong governance structures and strict compliance with Sharia principles function not merely as regulatory obligations, but also as strategic instruments to enhance performance, resilience, and long-term sustainability of Islamic financial institutions in Indonesia.